Production of Wood-Plastic Composite from Mixed Particles of Pterocarpus angolensis (Mukwa) And Gmelina arborea (Roxb) - Atowon, A. D; Ita. , E.O.; Ededet, M. O. (International Journal of Computing and Engineering, 2023)
Purpose: It is increasingly difficulty to meet the demand and supply for solid wood for human difference end uses, in view of the alarming shrinkage of forest resource. But the un-ending in wood resource supply to wood-based industry basically continue to underscore the need to think beyond total dependent on solid wood. The study creates a template to ameliorate wood scarcity viz production of wood-plastic composite from mixed particles of Pterocarpus and Gmelina, further analysis the effect of particles size on the Physio-mechanical properties of composite. Methodology: Five sieved size were employed, polyester and Meth ether Ketone peroxide (MEKP) were used as adhesive and accelerator respectively, sieved samples were oven dried under a control temperature of 1020C to moisture content of 12 to 15%. Fabricated composite was machined according ASTM standards. Findings: The water absorption of composite S1, S2, S3 recorded higher water uptake compared to S4 and S5 composites. Experimental results of mechanical properties revealed progressive strength properties with sieved sizes, ranging from 23 KN/mm2 to 67KN/mm2 for compressive strength, while the tensile strength, ranged from 17KN/mm2 to 30KN/mm2. In addition, it was observed that, particle size has influence on the Physical and mechanical properties of composites. Unique contribution to theory, practice, and policy:The study hereby concluded that chips from the above species can be used for the production of composite to ameliorate the demand of solid timber from our ecosystem.